Produksi Mesenchymal Stem Cell (MSC) dari Sumsum Tulang Belakang Mencit - Rinendyaputri, Ratih; Noviantari, Ariyani (Central Basic Biomedical and Health Technology, 2015)
Mesenchymal Stem Cell (MSC) is a source of stem cells are multipotent that can be differentiated into many tipe of cells. MSC can be obtained from various sources one of which is from the bone marrow. But the number of MSCs in the bone marrow is very limited, thus requiring the production of MSC in vitro to obtain considerable amounts on the application or further research. The success of the production is very dependent on various factors such as isolation methods and the use of appropriate culture medium. This study aims to compare the Dulbeccos Modified Eagles Medium (DMEM) and Minimum Essential Medium Eagle (MEM) as a culture medium producing MSC were isolated from bone marrow of mice tibia and femur using flushing methode. Research conducted at the Laboratory of stem cells, Center for Biomedical and Basic Technology of Health. Tibia and femur of mice cleared of fat and decontaminated using alcohol 70% for 2 minutes. Once clean both ends of the bone is cut and in flushing using 1 cc needle with DMEM culture medium and MEM. Medium replacement is done after 48 hours of culture. The results showed that the MSC yield from tibia and femur bone marrow is higher when cultured with MEM rather than DMEM (p <0.05). In this study the production of MSC from bone marrow of mice can be performed by using MEM medium with flushing method.Key words: Isolation, Medium, Bone marrow, MSCÂ AbstrakMesenchymal Stem Cell (MSC) merupakan sumber stem cell yang bersifat multipoten sehingga mampu berdiferensiasi menjadi berbagai tipe sel. MSC dapat diperoleh dari berbagai sumber salah satunya adalah dari sumsum tulang. Namun jumlah MSC dalam sumsum tulang sangat terbatas, sehingga diperlukan produksi MSC secara in vitro untuk mendapatkan jumlah yang cukup pada aplikasi atau penelitian lebih lanjut. Keberhasilan produksi sangat bergantung pada berbagai faktor seperti metode isolasi dan penggunaan medium kultur yang tepat. Penelitian ini bertujuan untuk membandingkan medium kultur Dulbeccoâs Modified Eagleâs Medium (DMEM) dan Minimum Essential Medium Eagle (MEM) untuk produksi MSC yang diisolasi dari sumsum tulang tibia dan femur mencit dengan metode flushing. Penelitian dilakukan di Laboratorium stem cell, Pusat Biomedis dan Teknologi Dasar Kesehatan Badan Litbangkes. Tulang tibia dan femur mencit dibersihkan dari lemak dan didekontaminasi menggunakan alkohol 70% selama 2 menit. Setelah bersih kedua ujung tulang dipotong dan di flushing menggunakan jarum 1 cc dengan medium kultur DMEM dan MEM. Penggantian medium dilakukan setelah 48 jam kultur. Hasil menunjukkan bahwa jumlah MSC yang diperoleh dari sumsum tulang tibia dan femur mencit lebih banyak dengan MEM sebagai medium kultur dibandingkan dengan DMEM (p<0,05). Pada penelitian ini produksi MSC dari sumsum tulang mencit dapat dilakukan dengan metode flushing dengan menggunakan medium MEM.Kata kunci : Isolasi, Medium, Sumsum tulang, MSC